Metal organic frameworks for wastewater treatment, renewable energy and circular economy contributions - Simranjeet Singh; Nikhita Sivaram; Bidisha Nath; Nadeem A. Khan; Joginder Singh; Praveen C. Ramamurthy (npj Clean Water)
Abstract Metal-Organic Frameworks (MOFs) are versatile materials with tailorable structures, high surface areas, and controlled pore sizes, making them ideal for gas storage, separation, catalysis, and notably wastewater treatment by removing pollutants like antibiotics and heavy metals. Functionalization enhances their applications in energy conversion and environmental remediation. Despite challenges like stability and cost, ongoing innovation in MOFs contributes to the circular economy and aligns with Sustainable Development Goals.